PENGARUH PROFITABILITAS, KEBIJAKAN HUTANG, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PROPERTI DAN REAL ESTATE (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2020)
ABSTRACTÂ This research investigates the effect of profitability, debt policy, and liquidity on the value of the company on property and real estate companies in the Indonesian Stock Exchange. The data in this study is annual data with the period 2010 to 2016. The sampling method used is purposive sampling, which of the population of listed property and real estate companies in the Indonesia Stock Exchange are 49 companies, 32 companies selected as research sample. The independent variables in this research are profitability (ROE), liquidity (CR), and debt policy (DER). The dependent variable in this research is a firm value (PBV). The data analysis method used in this research is panel data regression analysis. The results showed that ROE, DER, and CR had a significant effect on PBV simultaneously. Partially ROE and DER have a substantial impact on PBV, whereas CR is having no considerable impact on PBV.Â Keywords: profitability, debt policy, liquidity, firm value